2023
DOI: 10.1155/2023/6685010
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation for Highway Geometric Design Based on Spatial Path Properties

Lu Wang

Abstract: Safety is an important aspect of road design. In highway geometric design, road engineers use a two-stage design method due to its convenience, but the available two-dimensional design tools on the market are believed to impose limitations. Horizontal and vertical alignment parameters are considered and determined at the designer’s discretion, potentially downplaying the three-dimensional characters of spatial curves. This study focuses on the three-dimensional characteristics of highway alignments and investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…It includes models that outline operating speeds across different alignment categories and clarifies the relationship between operating speed and accident rates. However, recent studies have indicated that categorizing the road alignment solely based on two-dimensional horizontal and vertical features overlooks the micro-variations in spatial geometric characteristics of the alignment [ 14 ]. The road alignment is essentially a three-dimensional spatial curve.…”
Section: Introductionmentioning
confidence: 99%
“…It includes models that outline operating speeds across different alignment categories and clarifies the relationship between operating speed and accident rates. However, recent studies have indicated that categorizing the road alignment solely based on two-dimensional horizontal and vertical features overlooks the micro-variations in spatial geometric characteristics of the alignment [ 14 ]. The road alignment is essentially a three-dimensional spatial curve.…”
Section: Introductionmentioning
confidence: 99%